Choosing outcome assessment tools in haemophilia care and research: a multidisciplinary perspective. Issue 1 (15th September 2016) - Fischer, K.; Poonnoose, P.; Dunn, A. L.; Babyn, P.; Manco‐Johnson, M. J.; David, J. A.; van der Net, J.; Feldman, B.; Berger, K.; Carcao, M.; de Kleijn, P.; Silva, M.; et al.
Abstract : Introduction: The implementation of early long‐term, regular clotting factor concentrate (CFC) replacement therapy ('prophylaxis') has made it possible to offer boys with haemophilia a near normal life. Many different regimens have reported favourable results, but the optimum treatment regimens have not been established and the cost of prophylaxis is very high. Both for optimizing treatment and reimbursement issues, there is a need to provide objective evidence of both short‐ and long‐term results and benefits of prophylactic regimens. Aims: This report presents a critical review of outcome measures for use in the assessment of musculoskeletal health in persons with haemophilia according to the International Classification of Functioning, Disability and Health (ICF). This framework considers structural and functional changes, activities and participation in a context of both personal and environmental factors. Methods: Results were generated by a combination of a critical review of available literature plus expert opinion derived from a two day consensus conference between 48 health care experts from different disciplines involved in haemophilia assessment and care. Outcome tools used in haemophilia were reviewed for reliability and validity in different patient groups and for resources required. Results and conclusion: Recommendations for choice of outcome tools were made according to the ICF domains, economic setting, and reason for use (clinical or research). The next step will be to identify a 'core' set of outcome measures for use in clinical care or studies evaluating treatment.